1999
DOI: 10.1046/j.1440-1673.1999.433671.x
|View full text |Cite
|
Sign up to set email alerts
|

Angiomyoma of the knee joint: Value of magnetic resonance imaging

Abstract: A case of angiomyoma as an unusual cause of knee pain is presented and the usefulness of magnetic resonance imaging in such a situation is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 1 publication
0
8
0
Order By: Relevance
“…There are no specific imaging techniques. However, as presented in our case, at US the lesion usually appears hypoechoic, clivated from the tendons, but MR can better delineate the lesion and define its relationship to the adjacent structures allowing a better pre-excisional planning [5]. Hwang et al [6] found that the smooth muscle and numerous vessels within vascular leiomyomas corresponded to hyperintense areas on T2-weighted MR images.…”
Section: Discussionmentioning
confidence: 59%
“…There are no specific imaging techniques. However, as presented in our case, at US the lesion usually appears hypoechoic, clivated from the tendons, but MR can better delineate the lesion and define its relationship to the adjacent structures allowing a better pre-excisional planning [5]. Hwang et al [6] found that the smooth muscle and numerous vessels within vascular leiomyomas corresponded to hyperintense areas on T2-weighted MR images.…”
Section: Discussionmentioning
confidence: 59%
“…The first comprehensive review of this rare tumor was published by Stout in 1937 [2]. To the best of our knowledge, to date, only two cases of intra-articular angioleiomyoma in the knee joint have been reported [3,4]. An angioleiomyoma can clinically resemble a glomus tumor because of episodic focal hyperesthesia, temperature sensitivity, and severe tenderness.…”
Section: Discussionmentioning
confidence: 99%
“…In general, angioleiomyoma is painful and located in the subcutaneous fat and fascia [1,2], but its intra-articular occurrence is extremely rare. To the best of our knowledge, only two such cases have been reported in English, and gadolinium (Gd)-enhanced magnetic resonance imaging (MRI) examination was performed in only one of them [3,4]. The atypical Gd-enhanced MRI image of our case compared with that of the more common angioleiomyoma arising in the subcutaneous fat may provide much preoperative information of this condition.…”
Section: Introductionmentioning
confidence: 93%
“…Magnetic resonance imaging findings in 37 patients with vascular leiomyomas in extremities[1][2][3][4][5][6][7][8][9][10][11][12][13][14] …”
mentioning
confidence: 99%